TRANSFORMASI BRAND RADIO BLAMBANGAN DI ERA DIGITAL: ANALISIS BRAND AWARENESS MELALUI KONTEN DIGITAL DAN NETWORKING - Yohandi; Anggie Rahmawati; Chintya Sari; Dwi Amelia Putri; Nurul Firdausiyah (Fakultas Dakwah Universitas Ibrahimy, 2026)
The development of digital technology has significantly transformed patterns of media consumption and directly affected the existence of radio as a broadcasting medium. The decline in radio listenership from the early 2000s to the 2020s indicates a shift from analog media to digital platforms. This study aims to analyze the brand transformation of Radio Blambangan 88.1 FM, a local government-owned radio station, in building brand awareness in the digital era through the utilization of digital content and networking. This research employs a descriptive qualitative approach, with data collected through semistructured interviews with internal radio stakeholders, digital content analysis, and documentary observation of collaborative activities and networking partnerships. The findings reveal that the brand transformation of Radio Blambangan extends beyond the digitalization of broadcasting through streaming and social media to include changes in communication strategies, the strengthening of its identity as a public radio station, and the enhancement of emotional closeness with audiences through personalized announcer interactions. Furthermore, networking with communities, institutions, and creative industry actors plays a crucial role in expanding reach and reinforcing the radio’s brand image. This transformation has proven effective in maintaining relevance and increasing the brand awareness of Radio Blambangan amid the dominance of digital media.